Content Analysis of Celebrity Culture on News Values in Nigerian Journalism - Ololade Olatunji Lateef; Muhammad Ridwan (Lakhomi Journal Scientific Journal of Culture, 2025)
This study explores the growing influence of celebrity culture on news values within Nigerian journalism. It investigates how media attention has increasingly shifted toward celebrity-related content, often at the expense of traditional journalistic priorities such as public interest, investigative depth, and civic responsibility. The study design is positivist while the research method is content analysis. The population of the study consists of the 310 newspapers operating in Nigeria while the sample size constitutes the three newspapers - The Nation, Daily Trust, and The Punch. Systematic random sampling is used for selecting articles for content analysis, ensuring every nth article within the selected timeframe is included in the sample. The main categories for analysis include story prominence (front page vs. other sections), tone (positive, negative, or neutral), framing (sensationalism, human interest, or factual reporting), and the type of celebrity featured (e.g., entertainers, athletes, politicians). The units of analysis will include individual articles, headlines, and the frequency of celebrity news. The data was presented using simple table, percentages and frequencies. Based on the findings, the study discovered that the types of celebrity stories on politics and business were not given prominent in the selected newspapers. The implication of the findings is that the selected newspapers pay more attention on other types of celebrity like sports and entertainment, which means that the surveillance function of the selected papers was not adequate as regards to celebrity stories within the study period.